DAMPAK PENYULUHAN PERTANIAN TENTANG TEKNIK PERSEMAIAN PADI (Oriza sativa L.) SISTEM DAPOG DI DESA TALKANDANG KECAMATAN KOTAANYAR KABUPATEN PROBOLINGGO - Ugik Romadi; Reinaldi Damasus Mite; Dwi Purnomo (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
Along with population growth, the need for food such as rice will continue to increase, which has an impact on the amount of per capita consumption. Therefore, every component that affects the level of production is very important to consider carefully. In 2016, the Ministry of Agriculture provided assistance to rice plant transplanter machines. Talkandang is one of the villages that received the machine. However, the use of the planting machine is still low or less than optimal in practice. This is due to the fact that farmers lack knowledge about the right way to sow the dapog system to prepare rice seeds to be planted using the planting machine. The purpose of this study was to determine the impact of extension on increasing farmer knowledge, attitudes, and skills. The method used in the study was a quantitative method and was analyzed descriptively using SPSS. The results showed that a) increased knowledge occurred before and after extension; Then in the skill aspect, it was found that 89% of the test results from the extension targets were in the skilled category. Furthermore, in the attitude aspect, 63% of the extension targets gave a positive response to the material provided.